All Days 2012
DOI: 10.2118/160242-ms
|View full text |Cite
|
Sign up to set email alerts
|

The First Implementation of Elongated Proppant for Hydraulic Fracturing in Russia

Abstract: The Volga-Urals basin is one of the largest oil-producing regions in Russia. Orenburg region, located in Volga-Urals, has more than 100 oil fields with great variety of formation properties. The majority of formation fluids are characterized by high gas/oil ratio (GOR) and high bubblepoint pressure. Today, most reservoirs are depleted and produce at bottomhole flowing pressure below bubblepoint pressure. These factors yield multiphase and non-Darcy flow in propped hydraulic fractures, which drastically decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…McDaniel et al 32 reported the first field implementation, proving the possibility of using elongated particles as proppant. The channel fracturing technology with rod‐shaped proppant has been conducted and achieved good performance in a lot of field tests around the world 33‐35 . Jia et al 36 established a mathematical model and concluded that compared with spherical proppants, rod‐shaped proppants have less embedment ratio and greater conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…McDaniel et al 32 reported the first field implementation, proving the possibility of using elongated particles as proppant. The channel fracturing technology with rod‐shaped proppant has been conducted and achieved good performance in a lot of field tests around the world 33‐35 . Jia et al 36 established a mathematical model and concluded that compared with spherical proppants, rod‐shaped proppants have less embedment ratio and greater conductivity.…”
Section: Introductionmentioning
confidence: 99%